(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The global adoption of renewable energy sources (RESs) is rapidly increasing to reduce greenhouse gas emissions. Algeria’s abundant solar energy makes it an ideal location for installing photovoltaic (PV) systems. This research examines the techno-economic feasibility of an off-grid microgrid system powered by solar energy, combined with a battery energy storage system (BESS) and a diesel generator (DG), to supply electricity to the rural community of Ghars Boughoufala in Ouargla province, southern Algeria. The proposed system incorporates a PV/BESS/DG configuration with bidirectional DC and AC buses and converters. The study employs a load-following (LF) energy management strategy (EMS) to maintain consistent energy distribution and power supply. Optimization of the proposed configuration was performed using the Wild Horse Optimizer (WHO) metaheuristic. WHO’s performance was compared with four cutting-edge algorithms. Results showed that WHO outperforms the other algorithms in terms of convergence speed and in minimizing life cycle cost (LCC) and cost of energy (COE), with the designed microgrid achieving an LCC of 7,229,644 USD and a COE of 0.3845 /kWh.